Increasing public confidence in Romanian probation system by developing the optimal social reintegration programmes for drink-driving offenders - Buta-Duțuc, Andra-Maria (European journal of probation, 2021)
The laudable evolution of the Romanian criminal punishment system from prison to non-custodial sanctions applied to drink-driving offenders is a sign of political and judicial institutional confidence, but the responsibility of becoming more and more efficient and trustworthy for the community still lies on Romanian probation. We examined the capacity of probation services in dealing with a considerably large number of drink-driving offenders and in developing specific rehabilitation programmes for them. Further on, we analysed whether there is a correspondence between the drink-driving offender’s profile and the intervention measures used. To succeed in this endeavour, we used the documentary analysis and the questionnaire method. To conclude, we noticed that the social reintegration programmes applied for drink-driving offenders in Romania generally correspond to the offender’s profile, but their application is hampered by the limited resources. Despite these impediments, the Romanian Probation System has gained the courts confidence and its position in the community has strengthened.